Manipulating a stated choice experiment. (September 2015) - Fosgerau, Mogens; Börjesson, Maria
Abstract: This paper considers the design of a stated choice experiment intended to measure the marginal rate of substitution (MRS) between cost and an attribute such as time using a conventional logit model. Focusing the experimental design on some target MRS will bias estimates towards that value. The paper shows why this happens. The resulting estimated MRS can then be manipulated by adapting the target MRS in the experimental design. Abstract : Highlights: Stated choice experiments can be manipulated through the design. A priori assumptions tend to be confirmed. These findings rely on the conventional logit model being misspecified. The paper shows how this can work.